2009
DOI: 10.1002/hbm.20672
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity in the default network during resting state is preserved in a vegetative but not in a brain dead patient

Abstract: The clinical and para-clinical examination of residual self-consciousness in non-communicative severely brain damaged patients (i.e., coma, vegetative state and minimally conscious state) remains exceptionally challenging. Passive presentation of the patient's own name and own face are known to be effective attention-grabbing stimuli when clinically assessing consciousness at the patient's bedside. Event-related potential and functional neuroimaging studies using such self-referential stimuli are currently bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
216
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(266 citation statements)
references
References 172 publications
(213 reference statements)
35
216
1
2
Order By: Relevance
“…The present work opens up the possibility that residual consciousness could be quantified by simply monitoring the dynamics of resting state activity. More specifically, it suggests that the mere presence of long-distance functional connectivity networks may not be a sufficient condition (50)(51)(52), as it may simply arise as a result of a shaping of nonconscious spontaneous activity by the preserved anatomical connectivity matrix. Rather, our results points to the importance of developing analytic tools to capture the dynamics of brain activity (26)(27)(28) and tentatively suggests that entropy of the state transition matrix, distance of each state to the underlying anatomical connectivity matrix, and presence of negative links may serve as useful candidate signatures of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…The present work opens up the possibility that residual consciousness could be quantified by simply monitoring the dynamics of resting state activity. More specifically, it suggests that the mere presence of long-distance functional connectivity networks may not be a sufficient condition (50)(51)(52), as it may simply arise as a result of a shaping of nonconscious spontaneous activity by the preserved anatomical connectivity matrix. Rather, our results points to the importance of developing analytic tools to capture the dynamics of brain activity (26)(27)(28) and tentatively suggests that entropy of the state transition matrix, distance of each state to the underlying anatomical connectivity matrix, and presence of negative links may serve as useful candidate signatures of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Activity in the two networks is normally anticorrelated -when one is active, the other is not [25]. However, studies using functional magnetic resonance imaging (fMRI) found decreasing anticorrelation in anesthesia [27], deep sleep [28], and VS/UWS [29], showing the anticorrelation to be a core constituent of conscious cognition [30].…”
Section: Disorders Of Consciousness and Neural Correlates Of Awarenessmentioning
confidence: 99%
“…2) [27]. Nevertheless, coherent DMN connectivity has also been observed in VS/UWS and anesthetized monkeys [29,36]. This suggests that the DMN may not be a strict reflection of conscious mental activity, and there are indications that the role of the DMN in consciousness is highly complex.…”
Section: Disorders Of Consciousness and Neural Correlates Of Awarenessmentioning
confidence: 99%
“…71,93,94 The best-studied network is the default mode network (DMN) encompassing the posterior and anterior cortical midline structures, which are considered to be involved in stimulus-independent thought, mind-wandering and self-consciousness. 95 The DMN was shown to be absent in brain death, 96 but still partially preserved in VS, [97][98][99] probably reflecting residual structural connectivity. 93 At the group level, resting-state network activity revealed reduced interhemispheric connectivity 100 and correlated with levels of consciousness in patients with DOC ( Figure 2).…”
Section: Functional Mrimentioning
confidence: 99%